(NaSTRONOMI^ESKIE NABL@DENIQ (B/s - (NuOKER(B, (NgORDONs; (NgURXQNOW(B, (Na(B.(N|(B.s; (NkUTYREW(B, (Na(B.(Ns(B.s; (NtOKOWININ(B, (Na(B. (Nas; (N}EGLOW(B, (Np(B. (Nw(B.s ((NmOSKWA (B:s (NmIR(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 325-346s
Keywords: (NaSTRONOMI^ESKIE NABL@DENIQs